Propagation of different components of cosmic rays from Centaurus A in the Galactic magnetic fields - Kobzar, O.; Hnatyk, B.; Marchenko, V.; Bogdan, T. (Advances in Astronomy and Space Physics, 2011)
Propagation of different chemical composition ultrahigh energy cosmic rays in the galactic magnetic fields was simulated. The simulation for the ultra high energy events, registered by the AUGER observatory in the sky region near Centaurus A was performed. It is shown that some of these events could originate from Centaurus A.